Addendum: Centrality dependence of high-pT D-meson suppression in Pb-Pb collisions at √sNN=2.76 TeV - Adam, Jaroslav; Angelov, Venelin; Arslandok, Mesut; Busch, Oliver; Deisting, Alexander; Glässel, Peter; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; Oeschler, Helmut; Ohlson, Alice; Oyama, Ken; et al. (Journal of high energy physics, 2017)
This is an addendum to the article JHEP 11 (2015) 205 [1]. The figures 3 (right), 4 (right) and 5 are updated with published results on non-prompt J/ψ-meson production from the CMS collaboration [2]. Open image in new window